Pelaksanaan Sistem Belanjawan Yang Diubahsuai di Kementerian Kerja Raya - Rosni, Julis (2004)
This research was conducted to study the implementation of Modified Budgeting System (MBS) at Ministry of Works (MOW). MOW was one of the pioneer ministry in the implementation of MBS. This research was conducted to determine the achievement of the objective of MBS and whether a proper method was being used in the preparation of cost in the Program Agreement. The role of Program/Activity Heads in determining input for the Program Agreement and the implementation as well as the weaknesses of the budgetary were also the focus of the study. Analysis was done to determine whether there was significant correlation between the achievement of MBS objectives in MOW and the top management commitment, officers attitude and skills in the implementation of the system. Study was also carried out to ascertain whether there are differences in the achievement of MBS based on officers’ experiences according to different units and sections. The data was obtained through self-administered questionnaire. The target population covered all seven programs with thirty activities under them. Data was analysed using descriptive and inferential statistics. This study indicated that the objectives of MBS were still not achieved and majority of the population used estimates rather than a proper method for determining output cost. However it was found the Program Heads played their role in determining the input for the Program Agreement. The major weaknesses in the implementation of MBS in MOW were the lack of training and exposure given to the officers involved in the implementation while the system was considered as not user friendly. Only the emphasis given by top management was significantly related to the achievement of the objectives of MBS. This research also showed that there was no significant difference in the achievement of the objectives between unit/section and experience in handling MBS. It is hoped that these findings would help the MOW and Treasury in the successful implementation of the system.